The Palace of Fine Arts (E.F. Clements)
On verso: The Palace of Fine Arts was built as part of the Great International Exposition of 1915 celebrating the opening of the Panama Canal. Restoration was pushed into the limelight in the early 50's by the Palace of Fine Arts League, resulting in private and city funds restoring this beautiful structure.